Characterization and modeling of kidney bean shell biochar as adsorbent for caffeine removal from aquatic environments - Bulduk İbrahim; Aşçıoğlu Çiğdem; Baydir Ayşegül Türk (Open Chemistry)
Caffeine, a widely consumed stimulant found in beverages like coffee, tea, and energy drinks, frequently contaminates surfaces and wastewater. This study explores the use of biochar derived from kidney bean (Phaseolus vulgaris) husks as a sustainable and cost-effective adsorbent for caffeine removal from aqueous solutions. The adsorbent was characterized using Fourier transform infrared spectroscopy for functional group identification, Brunauer–Emmett–Teller analysis for surface area and porosity, and scanning electron microscopy and energy-dispersive X-ray spectroscopy for morphological and elemental analysis. Batch adsorption experiments were optimized at an initial caffeine concentration of 50 mg/L, pH 7.0, 60 mg of adsorbent in 50 mL solution, and a contact time of 90 min. Kinetic modeling showed a strong fit to the pseudo-second-order model (R² = 0.999), suggesting chemisorption as the dominant mechanism. Isotherm analysis revealed monolayer adsorption behavior consistent with the Langmuir model (R² = 0.999), with a maximum adsorption capacity of 40.32 mg/g. These results demonstrate that kidney bean husk-derived biochar is an effective and environmentally friendly adsorbent for removing caffeine from water, offering promising applications in wastewater treatment.